2018
DOI: 10.18632/oncotarget.25526
|View full text |Cite
|
Sign up to set email alerts
|

A bi-specific inhibitor targeting IL-17A and MMP-9 reduces invasion and motility in MDA-MB-231 cells

Abstract: The cytokine IL-17A is associated with the progression of various cancers, but little is known about the molecular cross-talk between IL-17A and other tumor-promoting factors. Previous studies have shown that the IL-17A-mediated invasion of breast cancer cells can be inhibited by selective antagonists of the matrix metalloproteinase 9 (MMP-9), suggesting that the cross-talk between IL-17A and MMP-9 may promote cancer invasiveness and metastasis. Here, we present a novel strategy for developing cancer therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…The isolated TIMP-1 mutants showed an order of magnitude improvement in binding to MMP-3 catalytic domain (MMP-3cd). Although most of the focus for engineering TIMPs were focused on the N-terminal/inhibitory domain of TIMPs [103,251,252], it was shown that cooperation between Nand C-terminal domains of TIMP-1 improved binding to the target MMP-3.…”
Section: Timpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolated TIMP-1 mutants showed an order of magnitude improvement in binding to MMP-3 catalytic domain (MMP-3cd). Although most of the focus for engineering TIMPs were focused on the N-terminal/inhibitory domain of TIMPs [103,251,252], it was shown that cooperation between Nand C-terminal domains of TIMP-1 improved binding to the target MMP-3.…”
Section: Timpsmentioning
confidence: 99%
“…The TIMP interaction surface with MMPs contains six main regions (CTC motif at the N-terminus, AB-loop, Cconnector loop, GH-loop, EF-loop, and MTL-loop), which resemble monoclonal antibody (mAb) IgG The isolated TIMP-1 mutants showed an order of magnitude improvement in binding to MMP-3 catalytic domain (MMP-3cd). Although most of the focus for engineering TIMPs were focused on the N-terminal/inhibitory domain of TIMPs [103,251,252], it was shown that cooperation between N-and C-terminal domains of TIMP-1 improved binding to the target MMP-3.…”
Section: Timpsmentioning
confidence: 99%
“…Thus, cancer develops after migration to other anatomic sites, which are called secondary tumors ( 96 ). NF-kB key transcription factor plays a role in the expression and activity of MMPs ( 16 , 17 , 97 ). This, in turn, defines as many of the effects of IL-17A that are correlated with the TRAF-6-mediated activation of NF-kB.…”
Section: Il-17a//nf-kb/mmps Axis Promotes Bone Metastatic Breast Cancermentioning
confidence: 99%
“…As discussed earlier, IL-17A mediates cancer cell invasiveness and metastasis via MMP-2, MMP-9, and MMP-13. Furthermore, IL-17A stimulates MMP-9 mRNA expression, and MMP-9 inhibitors can inhibit the IL-17A-dependent invasion and metastasis of BCCs ( 17 ). The relation between IL-17A and its downstream MMP activity and breast cancer metastasis through MAPK and NF-Kb suggests the possibility of various strategies connected with blocking these checkpoints and kinase enzyme activity.…”
Section: Il-17 Signaling Cascade As a Therapeutic Target Of Breast Ca...mentioning
confidence: 99%
See 1 more Smart Citation